Snapdragons: teaching notes stage 1+ oxford reading tree - Howell, Gill (Oxford University Press London, 2003)
Provides a variety picture story books covering fiction required for Key Stage 1. "Snapdragons" series features a 24-page Teaching Notes booklet for each of the ten stages. There are teaching notes on each of the six stories in the stage covering: Group and Independent Reading Activities focusing on comprehension, speaking and other activities.